A taxonomic revision of the Neotropical spider genus Xiruana Brescovit 1997 (Araneae: Anyphaenidae, Anyphaeninae) - Oliveira, Luiz Fernando M.; Brescovit, Antonio D. (Zootaxa, 2015)
The genus Xiruana Brescovit, 1997 is currently composed of four South American species: X. gracilipes (Keyserling) from Brazil, Bolivia and Argentina, X. affinis (Mello-Leitão) from Brazil, X. hirsuta (Mello-Leitão) from Venezuela, Brazil, Paraguay, Argentina and Uruguay, and X. tetraseta (Mello-Leitão) from Venezuela, Brazil and Paraguay. Of these, the last three are redescribed in this paper, including the first description of the females of X. hirsuta and X. tetraseta. Additionally, we describe thirteen new species: Xiruana pocone n. sp. from Brazil, Paraguay and Argentina; X. bifida n. sp. from Brazil and Paraguay; X. aymara n. sp. from Bolivia; X. cocha n. sp. from Peru; X. fiebrigi n. sp. from Paraguay, and X. ajuricaba n. sp., X. tribarrense n. sp., X. guaia n. sp., X. jaboticabal n. sp., X. minacu n. sp., X. tapirape n. sp., X. lusitania n. sp., X. silarae n. sp., all endemic to Brazil. The known geographical distribution of all species here presented is mapped.